Bimbingan Rohani sebagai reduksi Stres pada Narapidana - Yunansa Firli Hasina; Puspita Sari (Da'wah Faculty of UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Islamic spiritual guidance is a program to convey spiritual values to prisoners carried out by spiritual guides (chaplains) in order to increase their faith and obligations so that they are able to face the problems faced by prisoners. The aim of this research is to determine spiritual guidance is a stress reduction for prisoners in class II B detention centers in Banjarnegara. This research uses qualitative field research to obtain data directly through research subjects obtained from prison employees and Islamic spiritual guidance officers (chaplains) at the class II B detention center in Banjarnegara. The results of this research show that this program process uses the basis of the Al-Qur'an and Hadith. Where the material is returned by the clergy to develop the material to suit the client's circumstances. The aim is to help prisoners determine the right direction to solve problems. Because it is not uncommon for someone to find it difficult to find a way out of a problem, especially when they are under pressure, bound by punishment, and do not have the right to do anything outside of prison. In the Banjarnegara detention center, there is an Islamic spiritual guidance program where the guidance itself is provided by prison officers, Ministry of Religion employees, and religious teachers from Islamic boarding schools in the Banjarnegara area, with a variety of materials and methods. The stress that many prisoners in the Banjarnegara Class IIB prison experience This Islamic spiritual guidance program must also be supported by the prisoner's awareness. If the prisoner has full confidence in successfully getting out of his problem. Bimbingan rohani Islam merupakan program untuk menyampaikan niai-nilai spiritual terhadap narapidana yang dilakukan oleh pembimbing rohani (rohaniawan) agar dapat menambah keimanan dan kewajibannya sehingga mampu menghadapi permasalahan yang dihadapi oleh narapidana. Penulisan penelitian ini bertujuan untuk mengetahui bimbingan rohani sebagai reduksi stress pada narapidana di Rutan kelas II B Banjarnegara. Penelitian ini menggunakan penelitian kualitatif bersifat lapangan untuk mendapatkan data secara langsung melalui subyek penelitian yang didapatkan dari pegawai rutan dan petugas bimbingan rohani Islam (rohaniawan) di di Rutan kelas II B Banjarnegara. Hasil penelitian ini bahwa Proses program ini menggunakan landasan Al-Qur’an dan Hadits. Dimana materinya dikembalikan lagi oleh rohaniawannya dalam mengembangkan materi dengan menyesuaikan keadaan klien nya. Tujuannya yaitu untuk membantu narapidana dalam menentukan arah yang benar untuk memecahkan masalah. Karena tidak jarang seseorang sulit untuk menemukan jalan keluar dari suatu masalah terlebih lagi dalam kondisi yang tertekan, sedang terikat hukuman, dan tidak memiliki hak untuk melakukan apapun di luar rutan. Di rutan Banjarnegara terdapat program bimbingan rohani Islam dimana bimbingannya sendiri diisi oleh petugas rutan, pegawai kemenag, dan ustadz dari pondok di daerah banjarnegara, dengan materi dan metode yang beragam. Kasus yang banyak dialami narapidana di rutan banjarnegara kelas IIB yaitu stress. Program bimbingan rohani Islam ini harus didukung juga oleh kesadaran narapidana tersebut. Jika narapidana memiliki keyakinan penuh akan keberhasilan keluar dari masalahnya.